Nationalism and ethnic conflict / edited by Michael E. Brown ... [et al.]. - Brown, Michael E. (An international security reader, 2001)
Most of the wars of the 1990s have been complex and bloody internal conflicts driven to a significant degree by nationalism and ethnic animosity. This book looks at how nationalism has affected these wars, and at ways to combat the problem.